Strategic planning is a tool for developing the reality of the Faculties of Arts and aligning with the labor market - Salim, Prof. Dr. Haitham Abbas; Jaber , Prof. Dr. Raja Sabbar (Thi Qar Arts Journal, 2024)
Strategic planning is considered a vital tool for the development of Arts Colleges in Iraq, as it helps to establish a clear and measurable vision and objectives that align with the colleges’ mission and future aspirations aimed at improving the quality of education and institutional development. This is achieved through analyzing the external and internal environment, such as evaluating infrastructure, teaching and learning resources, and the needs of students and the surrounding community. Strategic planning can identify opportunities and challenges faced by the colleges and develop strategies to deal with them. The importance of planning lies in the institution’s ability to align its educational outputs with the requirements of the job market and anticipate the skills and knowledge required from graduates. Colleges can develop educational programs that suit market needs and various sectors. These are implemented continuously with performance monitoring, evaluation, and adjustment as needed. This includes implementing development programs for faculty members and providing the necessary resources to improve the quality of education and scientific research. Strategic planning also encourages continuous communication with employers and relevant entities to ensure curriculum updates and effectively meet needs, increasing graduates’ employment opportunities and enhancing community development. The study concludes that strategic planning is an essential tool for the development of Arts Colleges in Iraq, as it helps direct efforts towards achieving educational and developmental goals that meet the needs of society and the job market effectively and sustainably.